PENGARUH KEBIJAKAN KEUANGAN PUBLIK KONVENSIONAL TERHADAP KESEJAHTERAAN MASYARAKAT - Dewi Citra Puspita Sari; Meyla Widiya Pratiwi; Rica Pebrianti; Reyhan Ahmad Ferenzo Thufail; Tri Eliza Handayani (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of conventional public financial policies on community welfare in Indonesia. Conventional public financial policies include fiscal policy (taxes and government spending), monetary policy, and national debt management policies formulated and implemented by the government. Community welfare as a dependent variable (Y) is measured through multidimensional indicators including the Human Development Index (HDI), poverty rate, unemployment rate, access to health and education services, and income distribution (Gini Index). The study uses a quantitative approach with panel data regression covering data from 34 provinces in Indonesia for the period 2019–2023. The results show that fiscal policy has a positive and significant effect on improving community welfare (β = 0.427; p < 0.05), while excessive public debt negatively impacts long-term welfare indicators. This study emphasizes the need for structural reforms in public financial management so that its benefits are more equitable and sustainable for all segments of society.